Hamiltonian map approach to 1D Anderson model - Kaya, T. (SPRINGER, 2009)
A one-dimensional diagonal tight binding electronic system is analyzed with the Hamiltonian map approach to study analytically the inverse localization length of an infinite sample. Both the uncorrelated and the dichotomic correlated random potential sequences are considered in the evaluations of the inverse localization length. Analytical expressions for the invariant measure or the angle density distribution are the main motivation of this work in order to derive analytical results. The well-known uncorrelated weak disorder result of the inverse localization length is derived with a clear procedure. In addition, an analytical expression for high disorder is obtained near the band edge. It is found that the inverse localization length goes to 1 in this limit. Following the procedure used in the uncorrelated situation, an analytical expression for the inverse localization length is also obtained for the dichotomic correlated sequence in the small disorder situation.
Keywords: LOCALIZATION-DELOCALIZATION TRANSITION; RANGE CORRELATED DISORDER; BINARY-ALLOYS; ABSENCE; DIFFUSION; CHAINS; Physics